(untitled) (Journal of Engineering, 2012)
teen sites Baghdad are made. The sites are divided into two groups, one in Karkh and the other in Rusafa. Assessing the underground conditions can be occurred by drilling vertical holes called exploratory boring into the ground, obtaining soil (disturbed and undisturbed) samples, and testing these samples in a laboratory (civil engineering laboratory /University of Baghdad). From disturbed, the tests involved the grain size analysis and then classified the soil, Atterberg limit, chemical test (organic content, sulphate content, gypsum content and chloride content). From undisturbed samples, the test involved the consolidation test (from this test, the following parameters can be obtained: initial void ratio eo, compression index cc, swelling index cs , coefficient of consolidation cv , coefficient of volume change mv, maximum preconsolidation stress Pc , Effective overburden pressure Po )and shear test (the following parameters can be obtained: undrained cohesion cu, angle of friction φ. In-situ testing was carried out by the standard penetration test in order to obtain the penetration resistance of the soil strata in a bore hole. Database for Baghdad soils is made using different GIS techniques connecting the spatial locations of those soils with their properties (ِAtterberg Limits, Specific Gravity, Grain size Analysis, Shear Strength parameters, Consolidation parameters), Borehole log, Site profile using the attribute tables, hyperlinks, metadata and SQL (System Query Language), so GIS techniques give the facilities for adding, editing and analyzing the existingdata as well as the any future data of Baghdad soils.